Mixed positive electrode material, positive electrode slurry, preparation method of positive electrode slurry, positive electrode plate and application of positive electrode plate

By adjusting the ratio of lithium manganese iron phosphate and lithium manganese oxide in the positive electrode material, and combining an optimized combination of conductive agents and binders, the problem of insufficient energy density and rate performance of the positive electrode material in the prior art is solved, and the improvement of high energy density and rate performance is achieved, while reducing costs and simplifying the production process.

CN119542379APending Publication Date: 2025-02-28XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411596760.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, while the combined positive electrode material of lithium manganese iron phosphate and lithium manganese oxide increases the energy density and rate performance, there are problems such as deterioration of material adhesion, high cost and complex production process.

Method used

By setting the weight ratio of lithium manganese iron phosphate to lithium manganese oxide to lithium manganese oxide from 7 to 8:3 to 2, using SP and carbon nanotubes as conductive agents, PVDF and HSV as binders, and optimizing dispersion and coating techniques during the preparation process, a hybrid cathode material with high energy density and high rate performance was prepared.

Benefits of technology

The energy density has been increased to above 190wh/kg, the rate performance has been greatly improved, and the compaction density has been increased to above 2.6kg/m3, while reducing costs and simplifying the production process.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a mixed positive electrode material, positive electrode slurry, a preparation method of the positive electrode slurry, a positive electrode plate and application. The mixed positive electrode material comprises the following components in parts by weight: 95-98 parts of an active substance, 1-5 parts of a conductive agent, 1-5 parts of a binder and 0-0.5 part of a dispersing agent, the active substance comprises lithium manganese iron phosphate and lithium manganate, and the weight ratio of the lithium manganese iron phosphate to the lithium manganate is (7-8): (3-2). According to the mixed positive electrode material, the minimum energy density can be increased to 190 wh / kg or above and the rate capability can be greatly improved through the ratio of the lithium manganese iron phosphate to the lithium manganate being (7-8): (3-2); meanwhile, the lithium manganese iron phosphate is large in specific surface area and small in compaction density, and the lithium manganate is small in specific surface area and large in compaction density, so that the use amount of a dispersing agent in a homogenizing section is reduced, the surface density fluctuation of a coating section is reduced, and the compaction density is increased to 2.6 kg / m < 3 > or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a mixed positive electrode material, a positive electrode slurry and a preparation method thereof, a positive electrode sheet and applications. Background Art

[0002] At present, the most common cathode materials on the market are lithium iron phosphate, ternary, lithium iron manganese phosphate, lithium iron manganese, etc. Most of the lithium iron manganese phosphate is prepared by mixing. The mainstream solution is to mix lithium iron manganese phosphate with ternary to improve energy density or safety. The secondary solution is to mix lithium iron manganese phosphate with lithium manganese oxide to improve the energy density of lithium manganese oxide.

[0003] The Chinese patent with publication number CN 115241441A discloses a mixed positive electrode slurry of lithium manganese iron phosphate and lithium iron manganese and a lithium battery. Although the use of lithium manganate as the main material reduces the cost, its energy density is greatly reduced. The Chinese patent with publication number CN113823765A discloses a lithium manganate / lithium iron manganese phosphate composite pole piece and lithium ion, which adopts a double-layer oblique coating method after the positive electrode material is nano-sized in advance. This method is too cumbersome and not conducive to large-scale production in the later stage. The Chinese patent with publication number CN 109524634A discloses a lithium-ion battery, which uses graphene and lignin to double-coat lithium iron manganese phosphate to prepare pole pieces, but this coating will cause the material adhesion to deteriorate, and it is necessary to reduce the proportion of active materials to increase the proportion of binders and thus reduce energy density. Summary of the invention

[0004] In view of this, one object of the present application is to provide a mixed positive electrode material, which can increase the energy density to more than 190wh / kg and greatly improve the rate performance by using a minimum ratio of 7-8:3-2 between lithium manganese iron phosphate and lithium manganate; at the same time, lithium manganese iron phosphate has a larger specific surface area and a smaller compaction density, while lithium manganate has a smaller specific surface area and a larger compaction density. The combination of the two can reduce the amount of dispersant used in the slurry stage, reduce the surface density fluctuation in the coating stage, and increase the compaction density to 2.6kg / m 3 In addition, compared with the existing pure lithium manganese iron phosphate and ternary-doped solutions, the energy density is not significantly reduced, but the cost is greatly reduced.

[0005] Another object of the present application is to provide a positive electrode slurry.

[0006] Another object of the present application is to provide a method for preparing positive electrode slurry.

[0007] Another object of the present application is to provide a positive electrode plate.

[0008] Another object of the present application is to provide a secondary battery.

[0009] Another object of the present application is to provide an electrical device.

[0010] To achieve the above-mentioned purpose, the first aspect of the present application proposes a mixed positive electrode material, comprising the following components in parts by weight: 95-98 parts of active material, 1-5 parts of conductive agent, 1-5 parts of binder, and 0-0.5 parts of dispersant; the active material comprises lithium iron manganese phosphate and lithium manganese oxide, and the weight ratio of the lithium iron manganese phosphate and the lithium manganese oxide is (7-8): (3-2).

[0011] In some embodiments, the conductive agent includes at least one of SP, carbon black, carbon nanotubes, and graphene.

[0012] In some embodiments, the conductive agent is a mixture of SP and carbon nanotubes in a weight ratio of (8-10):1.

[0013] In some embodiments, the binder includes PVDF and HSV.

[0014] In some embodiments, the binder is a mixture of PVDF and HSV in a weight ratio of (2-3):(8-7).

[0015] In some embodiments, the content of the dispersant in the mixed positive electrode material is 0.1-0.3 parts by weight.

[0016] The second aspect of the present application provides a positive electrode slurry, comprising the mixed positive electrode material described in the present application.

[0017] The third aspect of the present application provides a method for preparing a positive electrode slurry, characterized by comprising:

[0018] Dispersing the binder in an organic solvent to obtain a glue solution;

[0019] Adding the dispersant and the conductive agent into the glue solution for dispersion to obtain a first dispersion solution;

[0020] adding the lithium manganese iron phosphate into the first dispersion to obtain a second dispersion;

[0021] The lithium manganate is added into the second dispersion liquid and dispersed evenly to obtain the positive electrode slurry.

[0022] The fourth aspect of the present application proposes a positive electrode plate, including the mixed positive electrode material described in the present application; or, the preparation method of the positive electrode plate includes the positive electrode slurry described in the present application or the preparation method of the positive electrode slurry described in the present application.

[0023] The fifth aspect of the present application proposes a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet is the positive electrode sheet described in the present application.

[0024] The sixth aspect of the present application proposes an electrical device, comprising the secondary battery described in the present application.

[0025] The mixed positive electrode material described in this application can at least bring the following beneficial effects:

[0026] 1. Improved energy density: By using a minimum ratio of 7-8:3-2 between lithium manganese iron phosphate and lithium manganese oxide, the energy density can be increased to more than 190wh / kg and the rate performance can be greatly improved.

[0027] 2. Improved processing performance: Lithium iron manganese phosphate has a larger specific surface area and a smaller compaction density, while lithium manganate has a smaller specific surface area and a larger compaction density. The combination of the two can reduce the amount of dispersant used in the homogenization stage, reduce the surface density fluctuation in the coating stage, and increase the compaction density to 2.6kg / m 3 above.

[0028] 3. Cost reduction: Compared with the existing pure lithium manganese iron phosphate and ternary-doped solutions, the energy density is not significantly reduced, but the cost is greatly reduced.

[0029] 4. Improved rate performance: The excellent rate performance of lithium manganese oxide enables 3C discharge up to 100% after it is mixed with lithium iron manganese phosphate in the weight ratio of this application.

[0030] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION

[0031] The embodiments of the present application are described in detail below. The embodiments are exemplary and intended to be used to explain the present application, but should not be construed as limiting the present application.

[0032] In this application, the disclosure of numerical ranges includes all values ​​within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given in these ranges.

[0033] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.

[0034] In this application, weight can be understood as mass. Therefore, weight parts can be understood as mass parts, and weight ratio can be understood as mass ratio.

[0035] <Mixed positive electrode material>

[0036] The mixed positive electrode material of the embodiment of the present application includes the following components in parts by weight: 95-98 parts of active material, 1-5 parts of conductive agent, 1-5 parts of binder, and 0-0.5 parts by weight of dispersant; the active material includes lithium manganese iron phosphate and lithium manganese oxide, and the weight ratio of the lithium manganese iron phosphate to the lithium manganese oxide is (7-8): (3-2).

[0037] Illustratively, the content of the active material in the mixed positive electrode material includes, but is not limited to, 95 parts by weight, 95.5 parts by weight, 96 parts by weight, 96.5 parts by weight, 97 parts by weight, 97.5 parts by weight, or 98 parts by weight.

[0038] Exemplarily, the weight ratio of lithium iron manganese phosphate and lithium manganate includes but is not limited to 7:3, 7.2:2.8, 7.5:2.5, 7.75:2.25 or 8:2, etc. In the embodiment of the present application, the weight ratio of lithium iron manganese phosphate and lithium manganate is (7-8): (3-2), which can increase the energy density to 190wh / kg at the lowest and greatly improve the rate performance; if the weight ratio of lithium iron manganese phosphate and lithium manganate is less than 7:3, the energy density and compaction will be greatly reduced; if the weight ratio of lithium iron manganese phosphate and lithium manganate is greater than 8:2, the cost of the mixed material will be increased and the instability of the slurry will be increased.

[0039] As a preferred example, the active material consists of lithium manganese iron phosphate and lithium manganese oxide.

[0040] Exemplarily, the content of the conductive agent in the mixed positive electrode material includes but is not limited to 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight or 5 parts by weight, etc.

[0041] In some embodiments, the conductive agent includes but is not limited to at least one of SP, carbon black, carbon nanotubes, graphene, and the like.

[0042] As an optional example, the conductive agent is a mixture of SP (conductive carbon black) and carbon nanotubes. The carbon nanotubes may be at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, or few-walled carbon nanotubes. In the embodiment of the present application, the selection of a mixture of SP and carbon nanotubes is the only comprehensive means to improve conductivity and reduce costs.

[0043] As a preferred example, the conductive agent is a mixture of SP and carbon nanotubes in a weight ratio of (8-10): 1. Exemplarily, the weight ratio of SP and carbon nanotubes includes but is not limited to 8: 1, 8.5: 1, 9: 1, 9.5: 1 or 10: 1. In the embodiment of the present application, the SP and carbon nanotubes in the conductive agent are mixed in a weight ratio of (8-10): 1, which can achieve ideal conductivity without increasing the cost too much; if it is less than 8: 1, the manufacturing cost is increased and the electrical performance is excessive; if it is greater than 10: 1, the electrical performance is poor and has a greater impact on rate charge and discharge.

[0044] As a more preferred example, the conductive agent is a mixture of SP and carbon nanotubes in a weight ratio of 9:1.

[0045] Exemplarily, the mass percentage of the binder in the mixed positive electrode material includes but is not limited to 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight or 5 parts by weight, etc.

[0046] In some embodiments, the binder includes PVDF and HSV. In the examples of the present application, PVDF and HSV are selected as the composition of the binder to complement their shortcomings, specifically in terms of cost, slurry stability, electrical performance, etc.

[0047] As an optional example, the binder is a mixture of PVDF and HSV in a weight ratio of (2-3): (8-7). Exemplarily, the weight ratio of PVDF and HSV includes but is not limited to 2:8, 2.25:7.75, 2.5:7.5, 2.75:7.25 or 3:7, etc. In the embodiment of the present application, PVDF and HSV are mixed in a weight ratio of (2-3): (8-7), which can bring the cost, processing performance, and electrochemical performance to the optimal level; if it is less than 2:8, the peeling force is poor, and the electrical performance of double charge, storage, and low temperature is poor; if it is greater than 3:7, the cost is increased and the slurry stability is poor.

[0048] As a preferred example, the binder is a mixture of PVDF and HSV in a weight ratio of 2.5:7.5.

[0049] Exemplarily, the content of the dispersant in the mixed positive electrode material includes but is not limited to 0, 0.1 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight or 0.5 parts by weight, etc. In the embodiments of the present application, the role of the dispersant in the mixed positive electrode material is to improve the processing performance of the material, and its content exceeds 0.5 parts by weight, which increases the cost and has an excessive role.

[0050] As a preferred example, the content of the dispersant in the mixed positive electrode material is 0.1-0.3 parts by weight.

[0051] In some embodiments, the dispersant includes, but is not limited to, at least one of polyester, polyether, polyolefin, polyacrylate, and the like.

[0052] The mixed positive electrode material of the embodiment of the present application can at least bring the following beneficial effects:

[0053] 1. Improved energy density: By using a minimum ratio of 7-8:3-2 between lithium manganese iron phosphate and lithium manganese oxide, the energy density can be increased to more than 190wh / kg and the rate performance can be greatly improved.

[0054] 2. Improved processing performance: Lithium iron manganese phosphate has a larger specific surface area and a smaller compaction density, while lithium manganate has a smaller specific surface area and a larger compaction density. The combination of the two can reduce the amount of dispersant used in the homogenization stage, reduce the surface density fluctuation in the coating stage, and increase the compaction density to 2.6kg / m 3 above.

[0055] 3. Cost reduction: Compared with the existing pure lithium manganese iron phosphate and ternary-doped solutions, the energy density is not significantly reduced, but the cost is greatly reduced.

[0056] 4. Improved rate performance: The excellent rate performance of lithium manganese oxide enables 3C discharge up to 100% after it is mixed with lithium iron manganese phosphate in the weight ratio of this application.

[0057] <Positive electrode slurry and preparation method thereof>

[0058] The positive electrode slurry of the embodiment of the present application includes the mixed positive electrode material of the embodiment of the present application.

[0059] The method for preparing the positive electrode slurry of the embodiment of the present application comprises the following steps:

[0060] S101, dispersing the binder in an organic solvent to obtain a glue solution.

[0061] In some embodiments, the weight ratio of the binder to the organic solvent is (0.4-0.8):(9.6-9.2), including but not limited to 0.4:9.6, 0.5:9.5, 0.6:9.4, 0.7:9.3 or 0.8:9.2, etc.

[0062] Exemplarily, the organic solvent in step S101 includes N-methylpyrrolidone (NMP) or the like.

[0063] S102, adding the dispersant and the conductive agent into the glue solution for dispersion to obtain a first dispersion.

[0064] S103, adding the lithium manganese iron phosphate into the first dispersion to obtain a second dispersion.

[0065] S104, adding the lithium manganese oxide into the second dispersion liquid and dispersing it evenly to obtain the positive electrode slurry.

[0066] The method for preparing the positive electrode slurry of the embodiment of the present application, in addition to the beneficial effects of the mixed positive electrode material of the embodiment of the present application, can also bring at least the following beneficial effects:

[0067] Since the binder is first prepared into a glue solution, and then the dispersant and the conductive agent are added, and the lithium manganese iron phosphate and lithium manganate are added for the last time, the conductive agent can be dispersed first so that it can better and evenly coat the positive electrode particles later.

[0068] <Positive electrode>

[0069] The positive electrode plate of the embodiment of the present application includes the mixed positive electrode material of the embodiment of the present application; or, the preparation method of the positive electrode plate includes the positive electrode slurry of the embodiment of the present application; or, the preparation method of the positive electrode plate includes the preparation method of the positive electrode slurry of the embodiment of the present application.

[0070] In some embodiments, the method for preparing the positive electrode sheet comprises the following steps:

[0071] (1) The positive electrode slurry prepared by the positive electrode slurry preparation method of this embodiment is stirred at high speed and then subjected to inversion defoaming filtration to obtain a filtered positive electrode slurry.

[0072] (2) The filtered positive electrode slurry obtained in step (1) is transferred to a coating machine for coating and sheeting, and finally rolled, slit and die-cut to obtain small sheets, which are the positive electrode sheets of this embodiment.

[0073] In some embodiments, the method of reverse debubbling filtration in step (1) is: vacuum counterclockwise slow stirring.

[0074] Exemplarily, the speed of the high-speed stirring in step (1) is not less than 12 m / s, such as 13 m / s, 15 m / s, 18 m / s, 20 m / s or 25 m / s.

[0075] It should be noted that in the embodiments of the present application, there is no limitation on the selection of the current collector of the positive electrode plate, and it can be any positive current collector known in the art that can be used for secondary batteries.

[0076] <Secondary Battery>

[0077] The secondary battery of the embodiment of the present application comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet is the positive electrode sheet of the embodiment of the present application.

[0078] In some embodiments, the secondary battery is a lithium ion battery.

[0079] It should be noted that in the embodiments of the present application, there is no limitation on the selection of negative electrode plates, separators, electrolytes, etc., and they can be any negative electrode plates, separators and electrolytes known in the art that can be used in secondary batteries (especially lithium-ion batteries).

[0080] In some embodiments, the preparation method of the secondary battery of the embodiment of the present application includes: stacking the positive electrode plate, the separator and the negative electrode plate by a stacking machine or by hand, and then packaging and heat-sealing with aluminum-plastic film, baking in a furnace, injecting liquid, and chemically dividing the volume to obtain a finished battery.

[0081] <Electrical Devices>

[0082] The electric device according to the embodiment of the present application includes the secondary battery according to the embodiment of the present application.

[0083] Exemplarily, the above-mentioned electrical devices include electronic products such as mobile phones and tablet computers, power tools, new energy vehicles, etc.

[0084] Certain features of the present technology are further illustrated in the following non-limiting examples.

[0085] The HSV involved in the following examples and comparative examples is all HSV900.

[0086] 1. Examples and Comparative Examples

[0087] Example 1

[0088] (Mixed positive electrode material)

[0089] The mixed positive electrode material of this embodiment is composed of the following components in parts by weight: 97 parts of active material, 2.2 parts of conductive agent, 1.8 parts of binder, and 0.2 parts of dispersant.

[0090] The active material is composed of lithium manganese iron phosphate and lithium manganese oxide, and the weight ratio of lithium manganese iron phosphate to lithium manganese oxide is 7:3.

[0091] The conductive agent is a mixture of SP and single-walled carbon nanotubes at a weight ratio of 9:1.

[0092] The binder is a mixture of PVDF and HSV in a weight ratio of 1:3.

[0093] The dispersant was polyvinylpyrrolidone (PVP).

[0094] (Preparation of positive electrode slurry)

[0095] The preparation method of the positive electrode slurry of this embodiment, wherein the positive electrode material in the positive electrode slurry is a mixed positive electrode material, comprises the following steps:

[0096] (1) Dispersing a binder in an organic solvent NMP under stirring to obtain a glue solution, wherein the weight ratio of the binder to the organic solvent is 0.6:9.4.

[0097] (2) Adding a dispersant and a conductive agent to the glue solution obtained in step (1), stirring and dispersing the mixture evenly, and obtaining a first dispersion solution.

[0098] (3) Add lithium manganese iron phosphate to the first dispersion obtained in step (2), stir and disperse evenly to obtain a second dispersion.

[0099] (4) Add lithium manganese oxide to the second dispersion obtained in step (3), stir and disperse evenly to obtain the positive electrode slurry of this embodiment.

[0100] According to the test, the solid content of the positive electrode slurry of this embodiment is 61%, and the viscosity is 6000 mpa / s.

[0101] Example 2

[0102] This embodiment is basically the same as Embodiment 1, except that:

[0103] In the mixed positive electrode material, the weight ratio of lithium manganese iron phosphate and lithium manganese oxide is 3:1.

[0104] Example 3

[0105] This embodiment is basically the same as Embodiment 1, except that:

[0106] In the mixed positive electrode material, the weight ratio of lithium manganese iron phosphate and lithium manganese oxide is 4:1.

[0107] Example 4

[0108] This embodiment is basically the same as Embodiment 1, except that:

[0109] The content of the active material in the mixed positive electrode material was 95 parts by weight.

[0110] Example 5

[0111] This embodiment is basically the same as Embodiment 1, except that:

[0112] The content of the active material in the mixed positive electrode material was 98 parts by weight.

[0113] Example 6

[0114] This embodiment is basically the same as Embodiment 1, except that:

[0115] The mixed positive electrode material does not contain a dispersant.

[0116] Example 7

[0117] This embodiment is basically the same as Embodiment 1, except that:

[0118] In the mixed positive electrode material, the content of the conductive agent is 1 part by weight.

[0119] Example 8

[0120] This embodiment is basically the same as Embodiment 1, except that:

[0121] In the mixed positive electrode material, the content of the conductive agent is 5 parts by weight.

[0122] Example 9

[0123] This embodiment is basically the same as Embodiment 1, except that:

[0124] In the mixed positive electrode material, the content of the binder is 1 part by weight.

[0125] Example 10

[0126] This embodiment is basically the same as Embodiment 1, except that:

[0127] In the mixed positive electrode material, the content of the binder is 5 parts by weight.

[0128] Embodiment 11

[0129] This embodiment is basically the same as Embodiment 1, except that:

[0130] In the mixed positive electrode material, the content of the dispersant is 0.5 parts by weight.

[0131] Example 12

[0132] This embodiment is basically the same as Embodiment 1, except that:

[0133] In the mixed positive electrode material, the conductive agent is graphene.

[0134] Comparative Example 1

[0135] This comparative example is basically the same as Example 1, except that:

[0136] In the mixed positive electrode material, the weight ratio of lithium manganese iron phosphate and lithium manganese oxide is 3:2.

[0137] Comparative Example 2

[0138] This comparative example is basically the same as Example 1, except that:

[0139] In the mixed positive electrode material, the weight ratio of lithium manganese iron phosphate and lithium manganese oxide is 1:1.

[0140] Comparative Example 3

[0141] This comparative example is basically the same as Example 1, except that:

[0142] In the mixed positive electrode material, the weight ratio of lithium manganese iron phosphate and lithium manganese oxide is 9:1.

[0143] Comparative Example 4

[0144] This comparative example is basically the same as Example 1, except that:

[0145] The content of the active material in the mixed positive electrode material was 94 parts by weight.

[0146] Comparative Example 5

[0147] This comparative example is basically the same as Example 1, except that:

[0148] The content of the active material in the mixed positive electrode material is 93 parts by weight.

[0149] Comparative Example 6

[0150] This comparative example is basically the same as Example 1, except that:

[0151] In the mixed positive electrode material, the active material is lithium manganese iron phosphate.

[0152] Comparative Example 7

[0153] This comparative example is basically the same as Example 1, except that:

[0154] In the mixed positive electrode material, the active material is lithium manganese oxide.

[0155] 2. Performance Test

[0156] 1. Processing performance

[0157] The processing performance of the mixed positive electrode materials of each embodiment and comparative example was tested. The specific testing methods were: solid content and viscosity, fineness, viscosity rebound, coating appearance, peeling force, etc. of the output material.

[0158] 2. Cost accounting

[0159] The cost of the mixed positive electrode material of each embodiment and comparative example is calculated. The specific calculation method is: calculate the cost of the active material in the mixed positive electrode material of each embodiment or comparative example respectively.

[0160] 3. Electrochemical performance

[0161] The positive electrode slurries prepared in the examples and comparative examples were used to prepare positive electrode sheets, and assembled into lithium-ion batteries, and the energy density and 3C discharge performance of each lithium-ion battery were tested.

[0162] A method for assembling a lithium-ion battery comprises the following steps:

[0163] (1) Preparation of positive electrode sheets: The positive electrode slurry prepared in each embodiment or comparative example was dispersed at a high speed (line speed of 18 m / s) and then reversed to remove bubbles and filtered, and then transferred to a coating machine for coating and sheeting, and then rolled, slit and die-cut to obtain small sheets, namely positive electrode sheets. The positive electrode sheets used 12 μm conventional carbon-coated aluminum foil as the current collector.

[0164] (2) Preparation of negative electrode sheet: 96 parts by weight of negative electrode active material graphite, 1.4 parts by weight of carboxymethyl cellulose (CMC), 1 part by weight of SP, and 1.6 parts by weight of styrene-butadiene rubber (SBR) were mixed evenly, then inverted to remove bubbles and filtered, and then transferred to a coating machine for coating and sheeting, and then rolled, slit, and die-cut to obtain small sheets, namely the negative electrode sheet. The negative electrode sheet can use a 6μm thick copper foil as the current collector.

[0165] (3) Preparation of electrolyte: Ethylene carbonate (EC) and ethyl methyl carbonate (DEC) were mixed in a volume ratio of 3:7, and LiPF6 was added to form an electrolyte. The concentration of LiPF6 was 1 mol / L.

[0166] (4) Diaphragm selection: Single-sided ceramic diaphragm, in which the base membrane is a polypropylene film with a thickness of 9 μm and the thickness of the ceramic is 3 μm.

[0167] (5) Battery assembly: The positive electrode sheet, separator and negative electrode sheet are stacked by a stacking machine, and then packaged with aluminum-plastic film and heat-sealed, put into a furnace for baking, injected with liquid, and divided into volumes to obtain a lithium-ion battery.

[0168] The energy density test method is: 0.33C charge and discharge after the first cycle is completed.

[0169] The test method for 3C discharge performance is: 1C constant voltage charge to 4.2V, then 0.05C constant current full charge, and 3C discharge.

[0170] The above performance test results are shown in Table 1.

[0171] Table 1 Performance test results

[0172] Examples or Comparative Examples Energy density (Wh / kg) Mixed cost (yuan) 3C discharge (%) Processing performance Example 1 190 47000 100 excellent Example 2 192 47500 98 good Example 3 193 48000 97 good Example 4 190 46500 99 good Example 5 191 48000 97 good Example 6 193 47500 95 Difference Example 7 193 47500 96 good Example 8 191 47500 99 Difference Example 9 193 47500 96 good Example 10 191 47500 98 good Embodiment 11 192 47500 98 excellent Example 12 192 47500 99 good Comparative Example 1 187 46000 100 Difference Comparative Example 2 183 45000 100 Difference Comparative Example 3 197 49000 90 Difference Comparative Example 4 187 46000 100 good Comparative Example 5 185 45500 100 good Comparative Example 6 210 50000 92 Difference Comparative Example 7 160 40000 100 excellent

[0173] As can be seen from Table 1, by using the positive electrode active material of the embodiment of the present application to prepare the positive electrode slurry and assemble the lithium ion battery, compared with the positive electrode material and the assembled lithium ion battery of the comparative example, a higher energy density, better 3C discharge performance and processing performance can be obtained, while the cost is greatly reduced.

[0174] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0175] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0176] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A mixed positive electrode material, characterized in that: The invention comprises the following components in parts by weight: 95-98 parts of active material, 1-5 parts of conductive agent, 1-5 parts of binder and 0-0.5 parts of dispersant; the active material comprises lithium manganese iron phosphate and lithium manganate, and the weight ratio of the lithium manganese iron phosphate to the lithium manganate is (7-8): (3-2).

2. The mixed positive electrode material according to claim 1, characterized in that: The conductive agent includes at least one of SP, carbon black, carbon nanotubes, and graphene.

3. The mixed positive electrode material according to claim 2, characterized in that: The conductive agent is a mixture of SP and carbon nanotubes in a weight ratio of (8-10):

1.

4. The mixed positive electrode material according to claim 1, characterized in that: The binder comprises PVDF and HSV; and / or, The content of the dispersant in the mixed positive electrode material is 0.1-0.3 parts by weight.

5. The mixed positive electrode material according to claim 4, characterized in that: The binder is a mixture of PVDF and HSV in a weight ratio of (2-3):(8-7).

6. A positive electrode slurry, characterized in that: Comprising the mixed positive electrode material as described in any one of claims 1 to 5.

7. A method for preparing a positive electrode slurry as claimed in claim 6, characterized in that: include: Dispersing the binder in an organic solvent to obtain a glue solution; Adding the dispersant and the conductive agent into the glue solution for dispersion to obtain a first dispersion solution; adding the lithium manganese iron phosphate into the first dispersion to obtain a second dispersion; The lithium manganate is added into the second dispersion liquid and dispersed evenly to obtain the positive electrode slurry.

8. A positive electrode sheet, characterized in that: It comprises the mixed positive electrode material as described in any one of claims 1 to 5; or, the preparation method of the positive electrode plate comprises the positive electrode slurry as described in claim 6 or the preparation method as described in claim 7.

9. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, characterized in that: The positive electrode sheet is the positive electrode sheet as claimed in claim 8.

10. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 9.

Citation Information

Patent Citations

  • Lithium manganate / lithium manganese iron phosphate composite positive plate and lithium ion battery

    CN113823765A

  • Mixed positive electrode material and application thereof

    CN104134815A

  • Lithium ion battery

    CN109524634A

  • Lithium ion battery positive electrode slurry, preparation method thereof and lithium ion battery

    CN110797536A

  • Lithium manganese iron phosphate and lithium manganate mixed positive electrode slurry and lithium battery

    CN115241441A

Cited By

  • Lithium manganese iron phosphate positive pole slurry and preparation method thereof, positive pole piece and preparation method thereof, and lithium ion battery

    CN120998977A